Optimalisasi Pemanfaatan Instagram dalam Promosi Produk Tenun Kendra Sutera Sabilulungan, Tasikmalaya - Santi Susanti; Wahyu Gunawan (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
The Internet has driven a significant shift in product promotion and marketing, moving the trend from conventional to digital. Social media platforms, particularly Instagram, are now crucial for achieving broader consumer outreach. However, many Micro, Small, and Medium Enterprises (MSMEs) have yet to fully optimize these channels for promotion and marketing. A specific case is the Kendra Sutera Sabilulungan woven cloth artisans, placed in Tasikmalaya Regency. This MSME primarily depends on traditional marketing methods, such as direct delivery, workshop sales, and physical exhibitions. Although an Instagram presence exists, its utilization remains suboptimal. This Community Service Program (PPM) was enforced to enhance the partner's promotional skills and market expansion via Instagram. We employed a participatory-collaborative method, providing training and hands-on practice for Kendra Sutera’s management and artisans in creating relevant photo and video content. The intervention successfully increased participants' understanding of digital promotion and marketing, enabling the artisans to generate more engaging content for the platform. In conclusion, Instagram is an effective and efficient medium for promoting MSME products like woven fabrics, and sustainable mentoring is critical to ensure the consistent and relevant marketing of Kendra Sutera Sabilulungan's products moving forward.